An Eight-Channel MRI Head Coil Array for Enhanced MRI-Guided Transcranial Focused Ultrasound Imaging Performance - Adam Maunder; Melany Mclean; Samuel Pichardo; G. Bruce Pike; Fraser J. L. Robb; Ashwin K. Iyer; Nicola de Zanche (IEEE Access)
Magnetic resonance guided focused ultrasound (MRgFUS) thermal ablation is a new method of non-invasive neurosurgery that can benefit from improved MR imaging performance. The ultrasound transducer shields the radio-frequency field of the body coil, reducing transmit and receive sensitivity as well as reducing transmit homogeneity. To improve the quality of structural imaging and the MR thermometry used to guide lesioning, we propose a dedicated 8-element receive array designed to work within the water bath of the ultrasound transducer helmet. The array consists of dipoles, consisting of flexible twin lead conductors, that pierce the water bath interface membrane, which forms a watertight seal around the patient’s head. In transmit mode, with the array detuned, no change in the transmit efficiency or homogeneity was observed, and simulation demonstrated no significant change in the 10g averaged specific absorption rate (SAR). In receive mode, the mean receive sensitivity within the brain was 5.7 times higher than that of the body coil. FUS heating is unaffected by the coil array, as demonstrated by an unaltered spread of the temperature at the FUS focal point. Finally, the precision of thermometry was improved by a factor of 2.25 in results from phantom imaging and a similar amount in in-vivo imaging.